Removal of Hydrogen Sulfide from Biogas at the Pig Farm in Hartpang Village Using Ferric Hydroxide Made of Cement and Sand Mixed and Coated with Ferric Chloride and Sodium Hydroxide - SISOMPHOU, Somphan; SIPHAXAY, Khamphoungeun; SOULISOMBOON, Dee; SENGPASERT, Bouthamaly; MANIVANH, Nouphone; BINTHAVONE, Amphaphone (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The purpose of this research was to design and manufacture a filter to remove hydrogen sulfide from biogas at a pig farm in Hat Pang village using pellets of sand mixed with cement with a diameter of 1.5 cm and a length of 2 cm. coated with ferric chloride solution (FeCl3) and sodium hydroxide (NaOH) as an absorbent, contained in a packed column with an inner diameter of 4 inches and a length of 100 cm and leaving a space of 10 cm above. The biogas from the pig farm in Hat Pang has a concentration of hydrogen sulfide gas before passing through the tank of 2,918 ppm, a flow rate of 5 liters per minute, and a completely randomized design (CRD) of absorbent pellets with a diameter of 1.5 cm and a length of 2 cm. It was seen that the concentration of hydrogen sulfide gas at the outlet on the first day was reduced to 0 ppm by the amount of hydrogen sulfide gas in biogas after passing through the absorption pellets of sand mixed with cement coated with ferric chloride (FeCl3) and sodium hydroxide (NaOH) with a diameter of 1.5 cm and length of 2 cm. The absorption efficiency has increased by 100%. It was shown that the efficiency of hydrogen sulfide adsorption from biogas increased with the length of the adsorbed grain.